Oxidation/Reforming Methane Oxidation Processes Based on Dense Tubular La0.6Sr0.4Co0.2Fe0.8O3-d Membrane Reactor - Nie, Yanlong; Yi, Jianxin; Feng, Shaojie (Asian Journal of Chemistry, 2013)
An oxidation/reforming membrane reactor accompanied with dense tubular La0.6Sr0.4Co0.2Fe0.8O3-d (LSCF) and Ni/g-Al2O3 reforming catalyst was used for methane conversion to syngas. The reaction processes was identified by comparing reaction behaviour in the membrane reactor and a blank reactor without catalyst in details. At 900 ºC, the methane conversion reached up to 33 %, CO selectivity (SCO) was almost 100 %, H2/CO molar ratio in effluent was 1.9-2.1 with membrane inner surface area 4.1 cm2, FHe = 30 mL·min-1, FCH4 = 2 mL min-1. The XRD and SEM results confirmed that the perovskite structure of LSCF membrane was preserved during the reaction. The structure stability of LSCF membrane owe to the moderate methane oxidation reaction in membrane stage.